German Influences in Colombia and their Current Exhortation to Psychologists - Ramírez Tobón, John Alejandro (Pensando Psicología, 2014)
Germany represents a worldwide reference in many fields of human knowledge, especially in science and the humanities. This essay attempts to explain how Germany, from the end of the 19th century to the 1970s, influenced Colombia in three fields of humanities: philosophy, psychology and pedagogy. These three closely related disciplines were enriched by German knowledge and the advances of such prominent figures as Nietzsche, Heidegger, Wundt and Franziska Radke. This article relates the influence of each of these figures to a specific discipline. At the end of the essay, the contributions of Nietzsche and Heidegger are revisited and thus become the central argument of this piece in explaining the continued validity of both approaches in current-day Colombia. Thus the “incarnation” of the forgetting of being proposed by Heidegger, and the reclaiming of the human put forward by Nietzsche are affirmed. Furthermore, an invitation is extended to psychology, based on the thinking of both philosophers, to propose alternatives from its research practice or intervention that promote this “return to being”, interpreted in this text as a “return to the human”. In this sense, the role of the psychologist is reaffirmed in a dehumanizing context such as that created by the Colombian conflict.
Keywords: Germany; Colombia; philosophy; pedagogy; psychology; a return to the human